Studies in the ancient Greek verbs in -skō - Zerdin, J; Zerdin, Jason (1999)
This thesis examines Ancient Greek verbs such as βάσκω, which are suffixed (mainly in the present tense) with -σκω. They present both morphological and semantic problems. Firstly, it is not clear why, beside simple -σκω, we have formations with reduplication such as γι-γνώ-σκω, and in -ίσκω as εύρ-ίσκω. Secondly, the presents in -σκω have been attributed four different meanings: causative, inchoative, iterative and zero. These functions are found separately for descendants of *-skelo- in other Indo-European languages, but Greek seems unique in showing all four at the same time. After a brief review of earlier scholarship (Chapter 1) and a summary account of the evidence for *-skelo- in other Indo-European languages (Chapter 2), this thesis offers a thorough examination of Greek verbs in -σκω in two well-defined corpora: Homer and Plato. Chapters 3 and 4 concentrate on the morphology and semantics of -σκω in Homer, and Chapters 7 and 8 concern these subjects in Plato. Chapter 5 discusses the so-called 'iteratives' in -(ε)σκω, found mainly in Homer and Herodotus. Two short sections (Chapters 6 and 9) summarise the situation in early and Classical Greek respectively. The detailed analysis highlights the distinctions between the early and Classical period. Although the Iliad and the Odyssey preserve features of the original formations, they also provide evidence for specific innovations, most notably presents with reduplication and in -ίσκω. It is possible, and even likely, that the iteratives in -(ε)σκυ have a common origin with presents in -σκω; but even in Homer they must be treated as a separate class. It emerges that semantically the forms in -(ε)<σκυ form a coherent category, probably marked by the feature '+REPEATED'; apparent contrasts in meaning are largely lexically determined. However, the main function of -σκω in Homer is that of creating presents from roots which originally yielded root aorists; the apparent causative / inchoative value is in fact based on the active / medio-passive contrast. In the Classical period, morphology and semantics move towards more regular patterns. The choice between reduplication, -ίσκω and -σκω is determined by stem-type, and we find two classes of minimal pairs: those of the form causative active μεθύσκω 'make drunk' : inchoative mediopassive μεθύσκομαι 'become drunk' : unmarked stative μεθύω 'be drunk', where the action is 'externally caused'; and those of the type inchoative active γενειάσκω 'become bearded' : stative γενειάω 'be bearded', where these is no causative alternant and the action is 'internally caused'.